Managing Tasks Across the Work-Life Boundary: Opportunities, Challenges, and Directions - Williams, Alex C.; Iqbal, Shamsi; Kiseleva, Julia; White, Ryen W. (2020)
ABSTRACT With the global shift towards remote work, understanding how people maintain their desired boundary has become critically relevant to HCI research at large. In this paper, we examine how people employed task management tools across the work-life boundary before the emergence of COVID-19. We report findings from a survey deployed to 150 information workers during Summer 2019 that inquired about task management tool usage, contextual task management practice, and preferences for separating work and nonwork. We first characterize and identify trends across tool use, job role, and task management practice. We find that the majority of task management activity occurs during work hours, and that information workers regularly managing work tasks beyond work hours and vice versa. We use the findings to inform new research questions that are pertinent to managing work-life boundaries in the context of the pandemic, its resulting stay-at-home orders, and more broadly, in the new future of work. CCS CONCEPTS • Human-centered computing → Human computer interaction (HCI); Empirical studies in HCI. KEYWORDS task management practices, work-life boundary, online survey. ABOUT THE AUTHOR/S Alex C. Williams University of Tennessee acw@utk.edu Alex C. Williams is a postdoctoral researcher in the School of Information and Computer Sciences at the University of California, Irvine. His research intersects the areas of human-computer interaction, machine learning, cognitive science, and workplace studies. He holds a PhD in Computer Science from the University of Waterloo. His dissertation research focused on designing and studying new systems for aiding people in the work-related transitions experienced in daily life. (https://acw.io) Shamsi Iqbal Microsoft Research shamsi@microsoft.com Shamsi Iqbal is a Principal Researcher in the Information and Data Sciences group at Microsoft Research AI, Redmond. Her primary research expertise is in the area of Attention Management for Multitasking Domains. Her work is motivated by the vision of transforming the field of productivity research in response to the changing technology landscape with an eye towards making people happy and satisfied with the process and the outcome. Currently she is focusing on how productivity is defined in the new era of multitasking and distraction, introducing novel ways of being productive and determining metrics for evaluating productivity. More specifically, she develops experiences and technology that helps people maintain focus when needed, but at the same time introduce new concepts of getting things done in limited focus environments. Julia Kiseleva Microsoft Research julia.kiseleva@microsoft.com Ryen White Microsoft Research ryenw@microsoft.com Ryen White is a Partner Research Manager at Microsoft Research AI, where he leads a large team of world-class scientists and engineers researching and developing intelligent experiences. In recent roles, Ryen led the applied science organization for Cortana and he served as chief scientist for Microsoft Health. Ryen’s research has focused on understanding search interaction and on developing tools to help people search more effectively. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).